Culture shock!, India - Kolanad Gitanjali (Singapore : Times Books International, 2004)
On social life and customs, etiquette, and culture shock of India.
Originally published: 1994.
Includes bibliographical references (p. 292-296) and index.
Keywords: Etiquette -- India; Culture shock -- India; India -- Social life and customs